GRADUATE PROFILE FORMATION FROM A MULTIPLE INTELLIGENCES PERSPECTIVE AT PONDOK MODERN DARUSSALAM GONTOR - Ulum, Bachrul; Sutiah; Fannani, Bakhruddin (Antis-Publisher, 2026)
Objective: This research analyses graduate profile formation based on Multiple Intelligences (MI) at Pondok Modern Darussalam Gontor (PMDG), addressing the persistent dichotomy between religious and secular education in Indonesia. Method: A systemic case study with 18 purposively-selected informants employed participatory observation (180+ hours), in-depth interviews, and documentation, analysed using Miles-Huberman-Saldaña and Braun-Clarke approaches with NVivo 14 software. Results: Three key findings emerged: (1) PMDG conceptualises graduate profiles by integrating Gardner's MI with tawhidi-holistic paradigms, positioning Spiritual and Moral-Character Intelligence as driving axes for seven other intelligences; (2) formation strategies comprise Total Education 24-hours, three-layer curriculum (100% religious + 100% secular), 5K Method (Modelling-Environment-Guidance-Habituation-Assignment), and five-dimensional holistic assessment; (3) impacts manifest across four multiplicative levels—individual character, institutional relevance, communal trust, and civilisational reform. Novelty: The MITH-E Model demonstrates MI theory adaptation within tawhid frameworks without losing scientific essence, providing the first comprehensive operational framework with concrete mechanisms and measurable indicators transferable to pesantren and madrasah globally.